Oxford Utilitarianism Scale: Psychometric Properties of a Spanish Adaptation (OUS-Spa) - Marcos Pascual-Soler; Jose Berrios-Riquelme; Raquel Gomez-Frias; Leynin Caamaño-Rocha; Dolores Frias-Navarro (SAGE Open)
This study aims to examine the psychometric properties of the Spanish adaptation of the Oxford Utilitarianism Scale (OUS-Spa) across three samples. The total sample consisted of 3,427 participants ( M  = 33.11 years; SD  = 13.68; 67% female), including respondents from Spain ( n  = 1,047), Chile ( n  = 1,039), and Colombia ( n  = 1,341). The results support the bifactor structure of the model, which includes the dimensions of Instrumental Harm and Impartial Beneficence, across all three samples. Measurement invariance was confirmed, and the scale demonstrated adequate internal consistency. Additionally, convergent validity was consistent with the psychological profiles associated with the subscales. These findings contribute to the literature on moral decision-making during times of heightened uncertainty, such as the early stages of the COVID-19 pandemic. Impartial Beneficence was positively associated with concerns about the coronavirus and perceptions of personal and global threat. Women scored higher on Impartial Beneficence, while men scored higher on Instrumental Harm. These patterns were consistently observed across all three samples. Older adults in Spain and Chile exhibited higher levels of Impartial Beneficence and lower levels of Instrumental Harm. Overall, the results support the validity of the Spanish version of the OUS, demonstrating a strong alignment with the original inventory.